Effect of radiotherapy on survival in advanced hepatocellular carcinoma patients treated with sorafenib: a nationwide cancer-registry-based study - Shou-Sheng Chu (Nature Portfolio, 2021)
Abstract Sorafenib is the standard treatment for advanced hepatocellular carcinoma (HCC) patients. This study aims to determine whether combining radiotherapy with sorafenib administration increases its efficacy. The study cohort included 4763 patients with diagnosed advanced HCC who received sorafenib between January 2012 and December 2015, as reported in medical records in the Taiwan Cancer Registry database. The effect of sorafenib with or without radiotherapy on survival was calculated using the Kaplan–Meier method and compared using the log-rank test. A Cox proportional hazards model was used for multivariate analysis. Patients receiving sorafenib plus radiotherapy had greater 1-year survival than did those receiving sorafenib alone (P < 0.001). Uni- and multivariate analyses also showed that radiotherapy increased survival after adjusting for confounders (adjusted HR 0.57; 95% CI 0.51–0.63). Further stratified analysis according to the timing of radiotherapy relative to sorafenib treatment revealed that patients who underwent radiotherapy after sorafenib had greater 1-year survival than did those undergoing radiotherapy within sorafenib use or sorafenib alone (adjusted HR 0.39; 95% CI 0.27–0.54). Combined treatment with sorafenib and radiotherapy results in greater HCC patient survival and should be considered an option for treating this challenging disease.